2016
DOI: 10.1007/s12020-016-1135-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in prevalence of obesity and high waist circumference over four years across European regions: the European male ageing study (EMAS)

Abstract: Diversity in lifestyles and socioeconomic status among European populations, and recent socio-political and economic changes in transitional countries, may affect changes in adiposity. We aimed to determine whether change in the prevalence of obesity varies between the socio-politically transitional North-East European (Łódź, Poland; Szeged, Hungary; Tartu, Estonia), and the non-transitional Mediterranean (Santiago de Compostela, Spain; Florence, Italy) and North-West European (Leuven, Belgium; Malmö, Sweden; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 45 publications
3
18
0
1
Order By: Relevance
“…In the present study, the lycopene content of fresh tomatoes is 53.21 mg/100 g dm or 2.94 mg/100 g of the product ( Table 1). These data are in agreement with the results of studies performed by other scientists [32,35,36], who found that the lycopene content of fresh tomatoes ranged from 0.88 to 7.74 mg/ 100 g of product. Alda et al [37] showed that the content of lycopene of fresh tomatoes was approximately 12 mg/ 100 g. Studies conducted in Hungary demonstrated that the average lycopene content of tomatoes accounted for 0.85 mg/100 g of product in winter, 1.10 mg in spring, and 13.6 mg/100 g of product in summer [35].…”
Section: Resultssupporting
confidence: 93%
“…In the present study, the lycopene content of fresh tomatoes is 53.21 mg/100 g dm or 2.94 mg/100 g of the product ( Table 1). These data are in agreement with the results of studies performed by other scientists [32,35,36], who found that the lycopene content of fresh tomatoes ranged from 0.88 to 7.74 mg/ 100 g of product. Alda et al [37] showed that the content of lycopene of fresh tomatoes was approximately 12 mg/ 100 g. Studies conducted in Hungary demonstrated that the average lycopene content of tomatoes accounted for 0.85 mg/100 g of product in winter, 1.10 mg in spring, and 13.6 mg/100 g of product in summer [35].…”
Section: Resultssupporting
confidence: 93%
“…But more recent studies and also the future prognosis show higher obesity prevalence among men than women in Europe [8,15,41]. The European male aging study concluded that weight and BMI are rising among men, especially in countries undergoing socioeconomic and political transitions [7]. It seems as though public health strategies applied the past most strongly influenced women living in Central and Western Austria.…”
Section: Western Austria Central Austria Eastern Austriamentioning
confidence: 99%
“…Today, most people worldwide live in countries where obesity kills more people than malnutrition. Epidemiological surveys indicate that the prevalence of obesity has clearly risen in recent decades [1][2][3][4][5][6][7][8][9][10][11]. Since 1975, the prevalence has nearly tripled globally [1], and the prognosis shows a steady increase in the obesity epidemic [12], which causes very high health care budgets [13].…”
Section: Introductionmentioning
confidence: 99%
“…5 Importantly, waist circumference (WC) in men is increasing more rapidly than body weight and body mass index (BMI). 6 Although both general and abdominal obesity are associated with an increased risk of premature mortality, 7 it has been shown that ab-dominal obesity may be a stronger risk factor for mortality than BMI. [8][9][10][11] Cardiovascular disease (CVD), diabetes, and kidney disease are among the leading causes of obesity-related death and disability-adjusted life years (DALYs, a measure of overall disease burden, expressed as the number of years lost due to ill health or disability).…”
Section: Introductionmentioning
confidence: 99%